2021
DOI: 10.1063/5.0064337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recirculation zones on the ventilation of a public washroom

Abstract: Air-borne transmission can pose a major risk of infection spread in enclosed spaces. Venting the air out using exhaust fans and ducts is a common approach to mitigate the risk. In this work, we study the air flow set up by an exhaust fan in a typical shared washroom that can be a potential hot spot for COVID-19 transmission. The primary focus is on the regions of recirculating flow that can harbor infectious aerosol for much longer than the well-ventilated parts of the room. Computational fluid dynamics is use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…It assumes that the infectious aerosol is uniformly distributed in the air contained in the room, and that the air in every part of the room is replaced at the same rate. This estimate can be grossly inadequate, as shown in a recent study (Sinha et al 2021).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…It assumes that the infectious aerosol is uniformly distributed in the air contained in the room, and that the air in every part of the room is replaced at the same rate. This estimate can be grossly inadequate, as shown in a recent study (Sinha et al 2021).…”
Section: Introductionmentioning
confidence: 93%
“…CFD simulations of this geometry are presented in a recent work (Sinha et al 2021), and a snapshot of the results are shown in Fig. 2.…”
Section: Geometry and Airflow Patternmentioning
confidence: 99%
See 2 more Smart Citations
“…Pourfattah et al [26] conducted a state-of-the-art review on the challenges in modelling and simulation of minimal particle dispersion such as airborne viruses or aerosols. Furthermore, researchers investigated the effect of natural ventilation and air circulation on various different scenarios of indoor airborne virus transmission [10,[27][28][29][30], including the effect of air purifiers [10]. Park et al 2021 [31] proposed natural ventilation strategies to prevent coronavirus transmission inside a school building.…”
Section: Introductionmentioning
confidence: 99%